Determinants of Local Commercial Banks’ Performance in Malaysia - Wee Jeng, Lee; Ramasamy, Suganthi; Rasiah, Devinaga; Yuen Yee Yen, Peter; Devi Pillay, Shalini (International Journal of Engineering and Technology, 2018)
Commercial banks play an important role in developing a countryâ€™s economy and maintaining its financial stability. Commercial banks will usually receive deposits from customers and lend out the money to people who need the money for their businesses or other legal purposes. Therefore, their performance is extremely important for a countryâ€™s financial stability and economic growth. This research examined the determinants of local commercial banksâ€™ performance in Malaysia. Performance was measured using Return on Asset, Return on Equity and Net Interest Margin. Using data from eight local commercial banks in Malaysia from tea 2006 to year 2015, this study found that credit risk, liquidity risk, bankâ€™s size and inflation rate significantly affect banksâ€™ performance.Â Â